2003
DOI: 10.1038/sj.bjc.6601298
|View full text |Cite
|
Sign up to set email alerts
|

Bax is essential for mitochondrion-mediated apoptosis but not for cell death caused by photodynamic therapy

Abstract: The role of Bax in the release of cytochrome c from mitochondria and the induction of apoptosis has been demonstrated in many systems. Using immunocytochemical staining, we observed that photodynamic therapy (PDT) with the photosensitiser Pc 4 induced Bax translocation from the cytosol to mitochondria, and the release of cytochrome c from mitochondria as early signalling for the intrinsic pathway of apoptosis in human breast cancer MCF-7c3 cells. To test the role of Bax in apoptosis, MCF-7c3 cells were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 54 publications
7
59
1
1
Order By: Relevance
“…DU-145 cells have been shown earlier to be re-sensitised by the ectopic expression of Bax to stimuli such as over expression or photodynamic therapy. 41,42 Likewise, GFP-Bax has been shown earlier to promote apoptosis similar to endogenous Bax. 3 To evaluate the levels of apoptosis in DU-145 cells and DU-145 cells expressing YFP-Bax, cells were seeded into 24-well plates, treated with 1 mM STS (6 h), 50 ng/ml TRAIL and 1 mg/ml CHX (6 h), or vehicle (DMSO, 6 h).…”
Section: Methodsmentioning
confidence: 99%
“…DU-145 cells have been shown earlier to be re-sensitised by the ectopic expression of Bax to stimuli such as over expression or photodynamic therapy. 41,42 Likewise, GFP-Bax has been shown earlier to promote apoptosis similar to endogenous Bax. 3 To evaluate the levels of apoptosis in DU-145 cells and DU-145 cells expressing YFP-Bax, cells were seeded into 24-well plates, treated with 1 mM STS (6 h), 50 ng/ml TRAIL and 1 mg/ml CHX (6 h), or vehicle (DMSO, 6 h).…”
Section: Methodsmentioning
confidence: 99%
“…PDT-treated MCF-7c3 cells showed cytochrome C release from mitochondria and apoptotic nuclei, whereas the latter cell type was not affected [99,100]. Also, treatment of MCF-7c3 cells with Bax antisense oligonucleotides reduced Pc 4-PDT induced apoptotic death and restoration of Bax expression in DU-145 cells restored apoptosis, indicating that the lack of Bax is responsible for the resistance of these cells to PDT-induced apoptosis [100]. However, the fact that Bax-negative DU-145 cells are as sensitive to Pc 4-PDT as MCF-7c3 cells, as determined by the clonogenic assay, indicates that the commitment to cell death occurs at a step prior to Bax activation.…”
Section: Role Of the Bcl-2 Family Of Proteins In Pdtmentioning
confidence: 99%
“…The responsiveness of the Bax knockdown is consistent with reports by Oleinick's group showing that absence of Bax, or of procaspase-3, did not protect cells from phototoxic effects of PDT using the phthalocyanine photosensitizer Pc 4. [3][4][5][6] Time sequence of autophagy and apoptosis A typical result after exposure of L1210 cells to an LD 90 PDT dose of CPO is shown in Fig. 5.…”
Section: Apoptotic and Cytotoxic Response To Pdtmentioning
confidence: 99%
“…2 It was later proposed that apoptosis was a means for the disposing of dead cells, but was not necessary for expression of the cytotoxic effects of PDT. [3][4][5][6] We originally proposed that the initiation of apoptosis by PDT, using a porphycene photosensitizing agent, derived from direct mitochondrial photodamage. 7 Later work revealed that the initial target of many photosensitizing agents was the anti-apoptotic protein Bcl-2, 8,9 a finding confirmed by Oleinick's group.…”
Section: Introductionmentioning
confidence: 99%